PIECES Framework for Information System Needs Analysis using Website-based Appsheet: A Technopreneurship Digitalization Solution in Indonesia - Nafiisa, Birra Lailatul; Jaswadi, Jaswadi; Djajanto, Ludfi (East Asian Journal of Multidisciplinary Research, 2024)
The development of technology and information systems hold crucial roles in the industrial world. The quantitative research aims to analyze information system needs as a reference in improving business processes and as a solution for digitizing technopreneurship in Indonesia. The object of this research is PT OMAJA POWER, a company operating in the renewable energy sector. The samples are selected using the side saturation method by which data is obtained through a questionnaire distributed to all company employees. The PIECES framework is employed to create a questionnaire and a system needs analysis. The research proposes a need analysis for an information system for managing account receivables and payables based on the PIECES framework which is expected to be central for technopreneurship in Indonesia. The research obtained the following percentages: 4.85% for performance, 4.76% for information and data, 4.76% for economics, 4.80% for control and security, 4.61% for efficiency, and 4.66% for service.